Copper-catalyzed borylative coupling of vinylazaarenes and N-Boc imines - Smith, Joshua J.; Best, Daniel; Lam, Hon Wai (Royal Society of Chemistry, 2016)
Cu-catalyzed three-component couplings of vinylazaarenes, B2(pin)2, and N-Boc imines are described. Oxidation of the initially formed boronate gives azaarene-containing, Boc-protected amino alcohols with reasonable to good diastereoselectivities.